Sex dependent regulation of immune responses in ex vivo lung slices - Patlin, Brielle Honor, author; Snow, Chris, advisor; Tobet, Stuart, advisor; Chanda, Soham, committee member (Colorado State University. Libraries, 2023)
Sex differences in respiratory disease have been increasingly obvious over the last several decades ranging from asthma, to interstitial lung disease, to the common cold. One way that lung functions are dependent on sex is in their immune responses to disease. While there are many factors that contribute to the severity of immune responses and recovery from illness, neuroimmune signaling is an understudied aspect. This could be partially caused by the difficulty of studying individual neuronal circuits in the periphery in live animals and the lack of necessary cell types in organoid or cell line models. To study these processes in the lung, an organotypic model, known as a precision cut lung slice (PCLS) can be utilized to maintain intracellular and extracellular signaling. The first study herein addresses the role of the most prevalently produced neuropeptide in the lung on immune, neuronal, and epithelial populations in the lung. This abundant neuropeptide, calcitonin gene related peptide (CGRP), generates several sex dependent responses in PCLS. With CGRP treatment, number of B cells, size of neuroendocrine bodies (NEB), and surfactant protein C (SPC) granule are higher in female PCLS. However, the number of CGRP immunoreactive fibers in female PCLS is lower than in male PCLS. These sex related changes of lung cell behavior may partially explain some disease susceptibilities and are important factors to consider in pharmaceutical development for respiratory diseases. PCLS can be used to test pharmaceutically relevant substances and drug delivery systems. The recent pandemic has made it evident that better ways to deliver pharmaceuticals to the lungs are required. Regarding this problem, a focus on nasal drug delivery is important. The current leading technology in this type of delivery mechanism involves utilizing lipid nanoparticles and nasal administration. However, this is not the most efficient way to treat the lungs. Crystallized protein structures have begun to be used for purposes other than determining protein structure. In the second study included here, protein crystals were loaded with biologically relevant molecules to purposefully induce immune responses, without causing an immune response by themselves. This functionality has a variety of benefits, because a primary problem in respiratory disease is over activation of the immune response. In this study, crystals were customized by loading different molecules (e.g., lipopolysaccharide (LPS)) and the immune modulatory affects were observable in PCLS. This generated a sex dependent immune response in PCLS, which was less over time than slices treated with pure LPS indicating a differential response over 48 hours. Using protein nanocrystals for pharmaceuticals may provide new ways to target respiratory disease by nasal delivery with benefits over lipid nanoparticles.